2007
DOI: 10.1080/00365520701251601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three bowel preparations on video-capsule endoscopy gastric and small-bowel transit time and completeness of the examination

Abstract: Bowel preparations for capsule endoscopy do not have a significant effect on gastric and small-bowel video capsule transit time and the rate of caecum visualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
2
30
1
3
Order By: Relevance
“…Some studies have demonstrated that bowel preparation has a negative influence on gastric emptying and intestinal transit time, but there is a lack of uniformity among their results. In fact, there is also evidence that bowel preparation has no effect on these parameters [7,15,16]. We did not observe differences in gastric or intestinal transit after any of the three preparations.…”
Section: Discussionmentioning
confidence: 45%
“…Some studies have demonstrated that bowel preparation has a negative influence on gastric emptying and intestinal transit time, but there is a lack of uniformity among their results. In fact, there is also evidence that bowel preparation has no effect on these parameters [7,15,16]. We did not observe differences in gastric or intestinal transit after any of the three preparations.…”
Section: Discussionmentioning
confidence: 45%
“…The results of the studies which investigated the effect of bowel preparation on CECR were not consistent with each other [15][16][17][18][19][20][21][22] , but improved image quality has been reported. Previous studies also investigated the role of endoscopic placement of capsule and/ or real-time viewing and showed that these approaches can improve CECR [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 81%
“…In principle, CE is a procedure that can only be performed in the fasting state [10]. In order to improve observational yield, diagnostic yield, and the large bowel arrival rate, a number of studies have been conducted using a variety of preparations (table 4) [5,6,7,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. However, studies evaluating the efficacy of MC as bowel preparation are currently very limited in number [22,24].…”
Section: Discussionmentioning
confidence: 99%